2008
DOI: 10.4319/lo.2008.53.1.0332
|View full text |Cite
|
Sign up to set email alerts
|

Could stratospheric ozone depletion lead to enhanced aquatic primary production in the polar regions?

Abstract: We study the effects of ozone depletion on primary production in ice-covered and open polar waters using a spectral radiative transfer model combined with a parameterization of the inhibition of marine photosynthesis by ultraviolet radiation. We find that ozone depletion might not have a negative influence on the aquatic algal community at high latitudes but instead could enhance primary production. For an ozone depletion of 50%, we estimate the yearly averaged enhancement to be about 1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…While there has been recent reports on stratospheric ozone depletions in the Arctic (Manney et al, 2011), generally, stratospheric ozone has been recovering over the past decades and this trend is expected to continue in the future (Coldewey-Egbers et al, 2014). Hamre et al (2008) showed that depletion in stratospheric ozone indeed results in elevated UV in sea-ice covered and open Polar waters; however it also results in increased PAR levels compensating negative effects of UV with overall minor effect on primary productivity, hence on optical properties influenced by particulate absorption and scattering. Therefore, it is unlikely that changes in stratospheric ozone as an external factor would play an important role for optical properties of seawater and marine ecosystem.…”
Section: Relevance Of a P (λ) And A Cdom (λ) To Underwater Light Distmentioning
confidence: 96%
“…While there has been recent reports on stratospheric ozone depletions in the Arctic (Manney et al, 2011), generally, stratospheric ozone has been recovering over the past decades and this trend is expected to continue in the future (Coldewey-Egbers et al, 2014). Hamre et al (2008) showed that depletion in stratospheric ozone indeed results in elevated UV in sea-ice covered and open Polar waters; however it also results in increased PAR levels compensating negative effects of UV with overall minor effect on primary productivity, hence on optical properties influenced by particulate absorption and scattering. Therefore, it is unlikely that changes in stratospheric ozone as an external factor would play an important role for optical properties of seawater and marine ecosystem.…”
Section: Relevance Of a P (λ) And A Cdom (λ) To Underwater Light Distmentioning
confidence: 96%
“…134 One contrasting study, however, suggested that the effects of ozone depletion on primary production of Antarctic phytoplankton, in ice-covered and open waters, might not be negative but instead could enhance primary production. 135 UV radiation induced photoinhibition of natural post-bloom phytoplankton diatom-dominated assemblages from temperate latitudes of Patagonia. The inhibition, however, decreased when samples were dominated by chlorophytes that are potentially a better quality food for grazers.…”
Section: Effects On Natural Phytoplankton Communitiesmentioning
confidence: 99%
“…Solar ultraviolet radiation (UVR, 280 to 400 nm) is an important environmental factor regulating microbial activities such as phytoplankton (Hamre et al 2008), bacterial production (Ogbebo & Ochs 2008) and viral growth (Fuhrman & Noble 1995). UVR can affect microbial organisms by damaging DNA (Buma et al 2001), reducing or increasing the availability of dissolved organic matter (DOM) and nutrients (Ziegler & Benner 2000), and inhibiting larger grazers (Medina-Sánchez et al 2006).…”
Section: Introductionmentioning
confidence: 99%